A Descriptive Qualitative Research: Islamic Values in Mandarese Oral Literature (Kalindaqdaq Masaala) - Rina Marliana; Achmad Taqlidul Chair Fachruddin (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
Kalindaqdaq is a famous oral literature in Mandarese Community in West Sulawesi. This research focused on Kalindaqdaq Masala which is themed on religion. Descriptive qualitative approach is used in this research to find out the Islamic Values in Kalindaqdaq Masala. There were 6 data which have been analized. The data showed that the order to perform Shalah in Islam is clearly implied in Kalindaqdaq Masala. This Research also showed that Kalindaqdaq Masala used as a media to spread the Islamic Values in West Sulawesi.